Cosmetic science and technology theoretical principles and applications - Sakamoto, Kazutami; Lochhead, Robert Y.; Maibach, Howard I.; Yamashita, Yuji (Elsevier, 2017)
Cosmetic Science and Technology: Theoretical Principles and Applications covers the fundamental aspects of cosmetic science that are necessary to understand material development, formulation, and the dermatological effects that result from the use of these products. The book fulfills this role by offering a comprehensive view of cosmetic science and technology, including environmental and dermatological concerns. As the cosmetics field quickly applies cutting-edge research to high value commercial products that have a large impact in our lives and on the world's economy, this book is an indispensable source of information that is ideal for experienced researchers and scientists, as well as non-scientists who want to learn more about this topic on an introductory level.--Provided by publisher.